State-business relations in Russia in the 2000s: From the capture model to a variety of exchange models? - Andrei Yakovlev (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
Using data from a 2009 survey of 957 manufacturing enterprises, this paper examines relations between the state and business as well as priority differences in the distribution of governmental support by federal, regional and local authorities. Regression analysis reveals that a "model of exchange" is the predominant pattern as opposed to "state capture" (in the case of big firms) or "grabbing hand" (in the case of SMEs), both of which were typical of the 1990s. However, there are some differences in priorities at different levels of government. The federal government in 2007-2008 provided more support to state-owned and mixed enterprises providing stable employment, while regional authorities more often supported firms that were pursuing modernization. These trends could pave the way for a shift in governmental policy at the regional level from "state capture"/"grabbing hand" to the Chinese-style "helping hand" model.
URN:NBN:fi:bof-201408072194
Keywords: D22; H25; H71; 330; state capture; state-business relations; Russia